Students' Self-Efficacy in Islamic Character Development: A Phenomenological Study of PAI Learning in the Merdeka Curriculum at Senior High Schools - Batula, Abu Warasy; Ritonga, Mhd. Aksaril Huda; Helmy, Helmy Abdullah; Supriadi, Udin; Zakaria, Zakaria (ISLAMIKA, 2025)
This study investigates the implementation of character education through Islamic Religious Education (Pendidikan Agama Islam, or PAI) in Indonesian schools, focusing on the development of students’ self-efficacy in internalizing moral values as prescribed by the Merdeka Curriculum, particularly in phases E and F. Employing an Interpretive Phenomenological Approach (IPA), the research involved 18 purposively selected students from three different school types in Bandung. Data collection was conducted through in-depth interviews, participatory observation, and focus group discussions. Analysis revealed four central themes: students’ internal struggles in cultivating moral self-control; the influence of social environments on collective efficacy; the emergence of moral agency within digital spaces; and the role of spiritual maturity in fostering authentic leadership. The findings demonstrate a developmental trajectory in students’ self-efficacy from initial efforts to resist negative behaviors (Phase E) to the embodiment of innovative, integrity-based leadership (Phase F). This study contributes to the theoretical expansion of self-efficacy by proposing the concept of “spiritual self-efficacy” and contextualizing Bandura’s four sources of efficacy within Islamic moral education. The results underscore that effective character education must move beyond mere transmission of moral knowledge to systematically fostering students’ confidence in consistently and authentically enacting moral behavior. These insights offer significant implications for advancing a more holistic and character-centered PAI curriculum and pedagogical strategy.